2009
DOI: 10.3391/ai.2009.4.3.8
|View full text |Cite
|
Sign up to set email alerts
|

First record of Branchiura sowerbyi Beddard, 1892 (Oligochaeta: Tubificidae) in Azores

Abstract: The kelp Undaria pinnatifida (Harvey) Suringar (Laminariales, Phaeophyceae), a native of Japan, northern China, and Korea, is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Branchiura predominated all through the year at a site close to the mouth of the Guareí River into the Paranapanema River and was associated with the water temperature. According to Raposeiro et al (2009), this species is thermophilic and lives at sites deficient in oxygen, such as stagnant water, with low depth and renewal (Brinkhurst & Jamieson, 1971). These characteristics are representative of the sites where they predominated.…”
Section: Discussionmentioning
confidence: 99%
“…Branchiura predominated all through the year at a site close to the mouth of the Guareí River into the Paranapanema River and was associated with the water temperature. According to Raposeiro et al (2009), this species is thermophilic and lives at sites deficient in oxygen, such as stagnant water, with low depth and renewal (Brinkhurst & Jamieson, 1971). These characteristics are representative of the sites where they predominated.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Lake Baikal showed that food availability was a limiting factor for Oligochaeta distribution in deep regions of the lake (Martin et al, 1999 (Real and Prat, 1992;Martin, 1996;Bonomi and Pasteris, 2006;Dornfeld et al, 2006) since they present adaptations allowing them to survive in less favourable conditions. Gills and respiratory appendages allow some species to survive in environments where oxygen is limited (Martin, 1996;Raposeiro et al, 2009). An example is the tubificid B. sowerbyi and the naidid D.…”
Section: Discussionmentioning
confidence: 99%
“…Branchiura sowerbyi is a cosmopolitan species and prefers lentic or slowly flowing warm waters, being originally from the tropical regions of Asia (Timm, 1980;Paunović et al, 2005;Raposeiro et al, 2009). This thermophilous tubificid is considered an invasive species and it is currently found in many countries in Europe (http://www.faunaeur.org).…”
Section: Discussionmentioning
confidence: 99%